Progress in cryptology -- AFRICACRYPT 2016 : 8th International Conference on Cryptology in Africa, Fes, Morocco, April 13-15, 2016, Proceedings /: 8th International Conference on Cryptology in Africa, Fes, Morocco, April 13-15, 2016, Proceedings. (2016) - Unknown
No abstract available